Collaborative Governance dalam Mewujudkan Wisata Halal di Aceh - Setiawan, Deni (Public Administration, Faculty of Politics and Social Science, Universitas Jenderal Soedirman, Indonesia, 2023)
Tourism development is an effort to take advantage of regional potential. Aceh Province is an area that has natural resources to promote tourism with the concept of halal tourism. This research will discuss Collaborative Governance in realizing Halal Tourism in Aceh. This study aims to explain the management of the concept of halal tourism with the Collaborative Governance approach from Ansell and Gash's theory. This study uses a qualitative descriptive method with a literature study approach. The results of this study indicate that halal tourism in Aceh is carried out by (1) Looking at the initial conditions, in this case, the local government provides initial ideas related to halal tourism and is responded to by stakeholders; (2) Facilitative leadership, in this case, the local government tries to provide and facilitate the needs of the halal tourism program to stakeholders; (3) The institutional design, in this case, the regional government or the Aceh Tourism Office, uses the Aceh Qanun Number 8 of 2013 as a reference in the halal tourism program, and; (4) The collaboration process, in this case, the Aceh Tourism Office holds a meeting with stakeholders to discuss halal tourism. Keywords: Collaborative Governance, Halal Tourism, Aceh